Narrativas de idosos moradores de cortiços em Santos: dilemas e encantamentos no cuidar - Muler, Gabriela [UNIFESP] (2021)
The present research emerged from concerns about my work as a professional at the Núcleo de Apoio à Saúde da Família (Family Health Support Center) in the care of elderly people living in tenements in the Central Region of the city of Santos. There are countless dilemmas in the act of taking care that appears when encountering the subjects that reside in that territory, dilemmas that permeate the history and organization of the territory, but also the life stories of the elderly who live there and the fine line between denying care, warding and caring by the professionals. In behalf of that, this study had as a guiding question to know the life stories of elderly residents of tenements in downtown Santos, understand their strategies of living in their daily basis and give visibility to these people and their issues. For that, the cartography method was adopted, having the experience as a foothold. From the meetings, narratives of the life stories of each elderly person were produced, bringing up issues and concerns that permeate the logic behind the action of taking care of. How to build guide about how to taking care of others? And if the other person does not agree with a behavior that I think is better, how do I respect his/her autonomy even in case of life-death? With this research, it was possible to realize that the act of storytelling makes it possible to keep the memories alive through storytellers and the listeners. And upon the narratives’ construction, rescue of memories, experiences and caring, it is possible to create realities that are more and more pleasurable to be lived, or at least not so much suffered by negligence and lack of watchful eye. The search for health care should not be based on responses to the high demands of professionals and the system, but on paths built with the subjects, through gaps in time that we touch, experience. And what is resolution when we talk about life? Taking care of maybe it ́s not the only solution.